ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN THE FIELD OF SUPERVISION AND CIVIL RECORDS IN THE LARGER FIELD - Neisya Khaera Cahyani; Taufik Purboyo; Emiraldo Win Pazqara (DYNAMICS: Journal of Public Administration, 2023)
The research entitled Analysis of Public Service Quality in the Population and Civil Registry Office in Banyumas Regency. This study aims to explain and describe the Quality of Public Services at the Population and Civil Registry Office in Banyumas Regency. This research uses qualitative methods with a descriptive approach. The qualitative approach is expected to be able to produce an in-depth description of speech, writing and behavior as well as an emphasis on observable subjective aspects of the subjects themselves. In qualitative research the authors determined the informants in this study were purposive sampling techniques. This research uses the theory from Parasuraman (2001: 26) which puts forward the concept of service quality related to satisfaction determined by five elements commonly known as "RATER" service quality (responsiveness, assurance, tangible, empathy and reliability). The data in this study was analyzed with an interactive analysis model consisting of four stages, namely data collection, data reduction, data display and drawing conclusions. From the results of this research, it is hoped that it can be useful to expand scientific understanding in social science disciplines, especially those related to the disciplines of state administration.